Comparative response of tall fescue and perennial ryegrass swards to variation in defoliation interval and height. Issue 4 (2nd October 2017) - Kaufononga, Salesi; Donaghy, Danny J.; Hendriks, Stacey J.; Matthew, Cory; Kemp, Peter D.; Cranston, Lydia M.
ABSTRACT: A plot study was undertaken to investigate the interactive effect of three defoliation intervals (one-leaf, two-leaf and three-leaf stage in perennial ryegrass (PR) and one-leaf, two-leaf and four-leaf stage in tall fescue (TF)) and two defoliation height residuals (low, 5 cm and high, 8 cm) on production parameters of TF compared with PR plots. DM yields, botanical composition and tiller densities of both species were all generally greater at the longest defoliation intervals (TF-4 and PR-3). However, this consistently resulted in the poorest herbage quality in the TF-4 treatment. The herbage quality was higher in TF-2 compared with TF-4; however, the DM yield, tiller density and proportion of sown species in the sward were reduced. It is not possible to achieve an adequate compromise between DM yield, botanical composition, tiller survival and herbage quality in TF, throughout the year, when defoliation occurs at the two-leaf and the four-leaf stages.